Physical activity status among health science students of Chitwan, Nepal - Adhikari, Kishor; Neupane, Sadikshya; Sapkota, Sachin; Khanal, Gayatri (Journal of Chitwan Medical College, 2021)
Background: Physical inactivity has become a major public health concern in todays’ world. Evidences suggest that nearly one-fifth of the overall risk for coronary heart disease, type 2 diabetes, breast cancer, colon cancer is due to physical inactivity. The aim of present study is to assess the physical activity status among health science students in Chitwan District of Nepal.Methods: Present study is a cross-sectional study conducted among health science students of Chitwan District identified through non-probability sampling technique. Ethical approval was obtained from CMC IRC. Information on physical activity was gathered using the self-reported Global GPAQ – 16 items. A final activity response from each student was summed into MET/minutes per week, which was further classified as: inactive, low active, moderately active and highly active in terms of total MET minute/week. Descriptive and inferential analysis was done through this IBM SPSS software version 20.Results: More than two-third of students reported their status as low active. Nearly 7% were physically inactive. About 93% of the health science students met the minimum WHO recommendation for physical activity (≥600 MET-minutes/week). The difference on physical activity status according to gender and age groups was found statistically significant (p